ANALISIS BIOMASSA DAN CADANGAN KARBON TANAMAN BAMBU BELANGKE (Gigantochloa pruriens) - Bambang Suprihatno; Rasoel Hamidy; Bintal Amin (Program Pascasarjana Universitas Riau, 2012)
The research was conducted from November 2011 to January 2012 in the mineral soil of Kebun Kayangan, PT Salim Ivomas Pratama to estimate the potential of carbon stock of the bamboo and to quantify the amount of carbon that can be absorbed by bamboo plants. Theresults of the research showed that carbon content of culm biomass from 50.68 to 54.87%(mean of 53.84%), leaf from 47.68 to 53.76% (mean of 51.47%) and twigs/branches from51,97 to 52,86 % (mean of 52.48%). The average of carbon content of the bamboo plantbiomass was 52.60%. Biomass obtained from the bamboo plants with different heights were145.07 g (1 m height), 461.33 g (3 m height), 834.79 g (5 m height), 999.24 g (7 m height),781.14 g (9 m height), 958.31 g (11 m height) and 1,925.67 g (12 m height). The average ofthe bamboo biomass was 872.22 g/individual. The potential of the bamboo biomass from23.47 to 29.82 t ha -1 with a mean of 26.30 t ha-1. Carbon stocks obtained from the bambooplants with different heights were 78.07 g C (1 m height), 248.04 g C (3 m height), 448.64 gC (5 m height), 541.68 g C (7 m height), 425.72 g C (9 m height), 519.67 g C (11 m height),1,029.79 g C (12 m height) and the average was 470.23 g C/individual. The potential ofcarbon stock of the bamboo ranged from 12.61 to 15.93 t C ha-1 with a mean of 14.08 t C ha -1. Total carbon stock in bamboo plantation were 52.55 t C ha-1, which was itemized asfollows : carbon stocks of bamboo 14.08 t C ha -1, under storey 0.11 t C ha-1, litter 2.83 t Cha-1 and soil 35.53 t C ha -1. Allometric equations to estimate of biomass according to high ofbamboo plant was Polynomial Y = - 520.31 + 684.62x – 113.76x2 + 6.0227x3 Y = biomass(g) and x = plant height (m). Allometric equations to estimate carbon stock according tohigh of bamboo plant was Polynomial Y = - 274.64 + 362.45x – 59.81x2 + 3.1594x3 Y =carbon stocks (g) and x = plant height (m).